(untitled)
Let L_2=(-Δ)^2+V^2 be the Schrödinger type operator, where V eq 0 is a nonnegative potential and belongs to the reverse Hölder class RH_q_1 for q_1> n/2, n≥ 5. The higher Riesz transform associated with L_2 is denoted by R= abla^2 L_2^-12 and its dual is denoted by R^*=L_2^-12 abla^2. In this paper, we consider the m-order commutators [b^m,R] and [b^m,R^*], and establish the (L^p,L^q)-boundedness of these commutators when b belongs to the new Campanato space Λ_β^θ(ρ) and 1/q=1/p-mβ/n. , number=1, journal=Analysis in Theory and Applications, year=2022, month=Dec., pages=99–110